Analysis of Electric Field and Current Density for Different Electrode Configuration of XLPE Insulation - Sunthrasakaran, Nishanthi; Akmal Mohd Jamail, Nor; Ezani Kamarudin, Qamarul; Gunabalan, Sujeetha (International Journal of Engineering and Technology, 2018)
The most important aspect influencing the circumstance and characteristics of electrical discharges is the distribution of electric field in the gap of electrodes. The study of discharge performance requires details on the variation of maximum electric field around the electrode. In electrical power system, the insulation of high voltage power system usually subjected with high electric field. The high electric field causes the degradation performance of insulation and electrical breakdown start to occur. Generally, the standard sphere gaps widely used for protective device in electrical power equipment. This project is study about the electric field distribution and current density for different electrode configuration with XLPE barrier. Hence, the different electrode configuration influences the electric field distribution. This project mainly involves the simulation in order to evaluate the maximum electric field for different electrode configuration. Finite Element Method (FEM) software has been used in this project to perform the simulation. This project also discusses the breakdown characteristics of the XLPE. The accurate evaluation of electric field distribution and maximum electric field is an essential for the determination of discharge behavior of high voltage apparatus and components. The degree of uniformity is very low for pointed rod-plane when compared to other two electrode configurations. The non- uniform electric distribution creates electrical stress within the surface of dielectric barrier. As a conclusion, when the gap distance between the electrodes increase the electric field decrease.Â Â